MicroRNAs in pathogenesis of breast cancer: Implications in diagnosis and treatment - Shah, Nirav R (Baishideng Publishing Group Co., Limited, 2014)
MicroRNAs (miRNAs) are small non-coding RNAs generated by a two-step complex process and are post transcriptional negative regulators of their target mRNAs. Dysregulation of many of these miRNAs has been associated with tumorigenesis in various cancers including breast cancer. Aberrantly high expression of specific miRNAs in breast cancer cells is demonstrated to be linked with inhibition of tumor suppressor genes and promote tumorigenesis. They are classified as oncogenic miRNAs. However, the tumor suppressor miRNAs are downregulated in breast cancer cells, since their major targets are oncogenic mRNAs. Understanding mechanism of action of specific miRNAs in breast cancer cells can be utilized to develop newer anti-cancer therapies. Recently, newer techniques are also developed to detect abundance of specific miRNA in the blood plasma samples and can be used in early diagnosis or prognosis in breast cancer. In this review article, we have discussed several miRNAs dysregulated in breast cancer and their therapeutic potential.